Sacral Pure Spinal Epidural Cavernoma Mimicing Schwannoma: Case Report - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2015)
Pure spinal epidural cavernomas are very rare pathologies. They constitute only 4% of all spinal epidural tumors. Their radiologic appearance may mimic many other spinal epidural pathologies such as schwannoma, meningioma, lymphoma, Ewing's sarcoma, chordoma, ependymoma, spinal angiolipoma, perineural cysts and disc herniation. Complete surgical resection is the preferred treatment. But unfortunately they usually bleed heavily during surgery that makes complete surgical resection difficult. Here we report a case of sacral pure spinal epidural cavernoma mimicking S1 root schwannoma. A 37 years old female patient presented with low back pain and radiculopathic symptoms. After MRI scans, the lesion was prediagnosed as S1 root schwannoma. Patient was operated and pathologic examination revealed that the lesion was a cavernoma. After surgical resection the patient' s symptoms completely disappeared and did not recur for 15 months.
Keywords: Spinal epidural cavernoma; sacral schwannoma; sacral schwannoma differential diagnosis; HEMANGIOMA